Letter (copy) : Basque Children - Tewson, Vincent
1941-01-23 038-0035-002 Secretary's. HVT/FC/134. 23rd January, 1941. Mr. T.M. Ferguson, Dundee & Dist. Union of Jute & Flax Wkrs., 69/71, Nethergate, DUNDEE. Dear Mr. Ferguson, BASQUE CHILDREN. I am in receipt of your letter of the 21st instant and shall be glad if you will convey to your Executive our best thanks for their generous donation of £50 to the International Solidarity Fund which, it is noted, they desire to be earmarked for the maintenance of Basque Children I can assure you that this contribution is much appreciated and will be used to the best possible advantage. Our official receipt is enclosed. Yours sincerely, Assistant Secretary. Receipt. 292/946/38/35(II)